Dimensionamento e análise de viabilidade econômica de um sistema de energia alternativo para o bloco Rio Canumã - FT/UFAM - Silva Neto, João Pedro Cantuária da (Brasil, 2024)
The Federal University of Amazonas (UFAM) - Senator Arthur Virgílio Filho University Campus, has been facing increasingly common problems related to the electricity supply, especially in the North Sector of the campus, which is located in an even more isolated region. The main alternative used by some sectors is to use a diesel motor generator set to overcome the problem. However, with growing investment in the potential for solar energy generation in Amazonas, it is necessary to explore the possibility of implementing a solar photovoltaic system, mainly because it is a cleaner source of generation compared to a diesel motor generator set. In this way, the proposed study aims to size an off-grid solar photovoltaic system with a hybrid inverter and a diesel motor-generator system in order to compare the economic viability of the two alternative energy systems. Both will be developed for the Rio Canumã block, located at the Faculty of Technology (FT), which does not yet have a solution for emergency supply of the environment's demands in the event of power outages (absence) provided by the local power utility. The loads of the chosen block are determined using an analytical method and a load analyzer to determine the total energy demand for the entire environment over a 6-hour period, ensuring an efficient, safe and functional system. Finally, we intend to present a quotation for the application of both systems and carry out an economic viability comparison, choosing the best solution presented.